HUBUNGAN MOBILITAS FISIK TERHADAP RISIKO JATUH PADA LANSIA DI MT HUSNUL KHOTIMAH TAHUN 2024 - Yani Christina; Nanang Rudy Utantyo; Fadhil Aulia Rahman (Universitas Batam, 2025)
ABSTRACT Background: The elderly experience a decline in physical function as they age, which can affect mobility and increase the risk of falling. Falls in the elderly can have serious consequences, including injuries and a decrease in quality of life. Limited physical mobility is one of the main factors contributing to fall incidents among the elderly. Methods: This study employed an observational analytic design with a cross-sectional approach. The study sample consisted of 50 elderly individuals selected using a total sampling technique. Data were collected through the Timed Up and Go (TUG) test to assess physical mobility and a fall risk questionnaire for the elderly. Data analysis was conducted using the chi-square test with a significance level of 0.05. Results: The results showed that among the 50 respondents, 66.0% had impaired physical mobility, 30.0% had good physical mobility, and 4.0% had normal physical mobility. Additionally, 88.0% of the elderly had a high risk of falling, while 12.0% had a low risk of falling. A significant association was found between physical mobility and fall risk among the elderly (p-value = 0.000). Conclusion: There is a significant relationship between physical mobility and fall risk in the elderly at MT Husnul Khotimah Masjid Raya Batam Center. Elderly individuals with limited mobility have a higher risk of falling Keywords: Physical Mobility, Fall Risk, Elderly